Importance of the Islamic Story Method in the Early Childhood Infusion of Morality - EKO YUSUF WAHYUDI; AAN FARDANI UBAIDILLAH (LPPM Sekolah Tinggi Ilmu Ushuluddin Darussalam Bangkalan Madura, 2021)
Using a descriptive qualitative approach, this study aims to describe how the Islamic storey method is being used to infuse moral religion into young children at TK TAAM Adinda Kepatihan Menganti Gresik, as well as what is supporting and obstructing this process. TAAM Adinda Kepatihan Menganti Gresik is a TK TAAM institution. From these findings, it can be deduced that the use of the Islamic storey method to infuse moral religion into TK TAAM Adinda Kepatihan Menganti Gresik is effective. When it comes to preparation, the educator has done both personal and technical things exceptionally well. Teachers use the model of development education gallop in RPPM (Rencana Pelaksaan Pembelajaran Mingguan/implementation plan of learning weekly/implementation plan of learning daily) as a result of the curriculum development 2013 containing about aqida, syari'ah, dan akhlak in order to teach students in the materialistic world about aqidah, syari'ah, dan akhlak. It is the educator's job to use a variety of methods to teach. In terms of media, the educator prefers to employ audio and visual media rather than storybooks and slates in their teaching. When it comes to assessing students, educators use methods such as question and answer sessions, direct observation, and discussions with parents and guardians. With the help of other educators, the environment, and learning itself, TAAM Adinda has implemented a method based on an Islamic storey to help instil moral values in the school's kindergarten population. Aside from a time barrier, management class, and tools to tell stories, there are additional factors. At the same time, both stimulants and deterrents have been operating.